ADVANTAGES OF MANUFACTURING ACCORDING TO INTERNATIONAL STANDARDS (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
Manufacturing medical devices according to international standards offers numerous advantages that extend beyond mere product quality improvement. One of the primary benefits is the enhancement of product quality itself, as standards like ISO 13485 establish rigorous process management and documentation protocols, ensuring consistent quality through continuous monitoring and efficient resource utilization. This not only builds consumer trust but also bolsters the brand's reputation.